Peningkatan Efek Sitotoksik Doxorubicin oleh Naringenin pada Sel Kanker Payudara T47D melalui Induksi Apoptosis - SENDY JUNEDI; RATNA ASMAH SUSIDARTI; EDY MEIYANTO (Fakultas Farmasi Universitas Pancasila, 2010)
Doxorubicin is one of the standard regiment for breast cancer chemotherapy, but resistance to this agent is often occured and long period usage will induce cardiotoxicity, Therefore, combination therapy (co-chemotherapy) is needed to improve the efficacy of doxorubicin and to reduce its systemic toxicity. Naringenin is one of the most abundant ilavonoids in citrus fruits which showed cytotoxicity in various human cancer cell lines and has mechanisms through pathways except p53. This research is aimed to examine the effect of naringenin in combination with doxorubicin against T47D breast cancer cell which is resistant to doxorubicin due to p53 mutation. The IC50 dan CI (combination index) values were detennined by the MTT assay, The apoptotic stimulation effect of narigenin and doxorubicin was performed by DNA staining using cthidum bromide-acridine orange. Naringenin and doxorubicin exhibited cytotoxic effect with IC50 of 509 µM and 15 nM, respectively. The CI value in all ratios of naringenin-doxorubicin showed synergistic effect (CI 0.20-0.89). Combination ofnaringenin-doxorubicin with concentration smaller than 12,5 µM-0.6 nM in 1:1 ratio exhibited an additive combination effect, The combined treatment increased the apoptotic effect of doxorubicin.These results show that naringenin is potential to be developed as co-chemotherapeutic agent with doxonibicin, although the molecular mechanism is still needed to be explored.